TGF-β1으로 자극한 사람중피세포주에서 조직플라스미노겐 활성제가 미치는 영향 - 이정림; Jung Lim Lee; 전수진; Soo Jin Jeon; 유영춘; Young Choon Yoo; 김지혜; Ji Hye Kim; 이유미; Yu Mi Lee; 권선중; Sun Jung Kwon; et al. (Tuberculosis and respiratory diseases, 2011)
Background: In an effort to find alternative therapeutic agents to prevent excessive fibrosis as a sequela to complicated parapneumonic effusion or empyema, we examined the effect of tissue plasminogen activator (tPA) as a fibrinolytic agent combined with talc or transforming growth factor (TGF)-β1 in a human pleural mesothelial cell line, MeT-5A. Methods: MeT-5A cells were stimulated with various doses of talc, doxycycline or TGF-β1 for 24 h and then were treated with tPA for an additional 24 h. Cell viability was measured by MTT assay. The production of interleukin (IL)-8 and vascular endothelial growth factor (VEGF) in the culture supernatants was measured by ELISA. Real-time PCR was carried out for measurement of type I collagen mRNA. Results: MeT-5A cells treated with talc showed a dose-dependent increase in production of IL-8. Talc also increased production of type I collagen mRNA at low doses, but talc did not influence the induction of VEGF. Addition of tPA to talc-stimulated cells showed further increases in the production of IL-8, but tPA did not influence the production of VEGF or type I collagen mRNA. TGF-β1 increased the production of both VEGF and collagen type I mRNA, both of which were effectively inhibited by additional tPA treatment in MeT-5A cells. Conclusion: TGF-β1 is a potent inducer of collagen synthesis without induction of IL-8 in MeT-5A cells. Addition of tPA after TGF-β1 stimulation inhibited further fibrosis by direct inhibition of collagen mRNA synthesis as well as by inhibition of VEGF production.